Unleashing the Power of Tomorrow: Exploration of Next Frontier With 6G Networks and Cutting Edge Technologies - Insha Ishteyaq; Khalid Muzaffar; Nawaz Shafi; Moath A. Alathbah (IEEE Access, 2024)
As societal needs evolve, especially with the advent of demanding applications like remote surgeries in Smart Health, current communication systems struggle to meet the required latency and reliability for such use cases. Similarly, enhancing existing applications, such as increasing transmission rates in mobile networks to provide Quality of Service (QoS) and improved user experiences, presents complex challenges. The pursuit of higher data rates has been realized by 5G wireless communication networks, which have already been commercially deployed. Nevertheless, the proliferation of smart communication devices and the emergence of IoE (Internet of Everything) applications present challenges to existing 5G networks in meeting the escalating requirements for ultra-reliable, low-latency communication. To address these limitations, researchers are focusing on the development of the sixth generation (6G) of cellular systems. Consequently, the selection of enabling technologies is crucial for designing a suitable 6G architecture that can address these evolving demands. Herein the main aim is to provide insights into the significant technologies for the future 6G, including their operation principles, potential applications, current research status, and associated technical challenges. This article proposes a methodology to analyze the relevance of enabling technologies and leverage it for designing an optimal 6G architecture. The evaluation results offer a unique perspective on 6G enablers, pinpointing issues and stimulating research for future mobile architectures. Additionally, the obtained insights provide researchers with essential information to stay updated on emerging enabling technologies and their suitability for crafting new and optimized 6G architectures that are engineered with adaptability and flexibility in mind, highlighting cell-free massive MIMO, hierarchical cell structures, and network slicing to facilitate ultra-reliable, low-latency communication and cater to various applications, all while prioritizing energy efficiency and sustainability.